2011
DOI: 10.1524/icom.2011.0026
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present, and Future of Model-Based User Interface Development

Abstract: This article presents the past, present and future of model-based user interface development. After 30 years of research there has been significant success in modeling user interfaces. This article aims to give a comprehensive overview of the history, describes important aspects and current approaches, lists actual challenges of model-based user interface development and gives implications for the next generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 1 publication
0
71
0
3
Order By: Relevance
“…With respect to conceptual work in the domain of model-based user interface descriptions that studies the various abstraction levels of user interface design [27,16], the main novel features of our interaction description language affect the level of the "Abstract User Interface 6 ." At this level, the descriptions of "Abstract Interaction Objects" [16] are independent of the concrete platform and interaction modality and are, rather, described in terms of their "semantics" [26].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to conceptual work in the domain of model-based user interface descriptions that studies the various abstraction levels of user interface design [27,16], the main novel features of our interaction description language affect the level of the "Abstract User Interface 6 ." At this level, the descriptions of "Abstract Interaction Objects" [16] are independent of the concrete platform and interaction modality and are, rather, described in terms of their "semantics" [26].…”
Section: Related Workmentioning
confidence: 99%
“…At this level, the descriptions of "Abstract Interaction Objects" [16] are independent of the concrete platform and interaction modality and are, rather, described in terms of their "semantics" [26]. While Paternò and Meixner refer to the semantics of user interfaces, we consider the semantics of the interaction itself and identified three concrete components, or dimensions, of the interaction semantics that we detailed in Section 4.2.…”
Section: Related Workmentioning
confidence: 99%
“…A thorough review of task models can be found in and a taxonomy for the comparison of task models has been developed by Meixner & Seissler (2011). In our chapter we focus on task models using the Concur Task Tree (CTT) notation as defined by Paternò et al (1997).…”
Section: Task Modelsmentioning
confidence: 99%
“…Especially the second factor, as also argued by Meixner & Seissler (2011), makes it advisable to specify interfaces on some sort of abstract level, from which operational code can be generated automatically, or at least in some semi-automated way. This aim is quite in contrast to traditional, mostly syntactic specification levels.…”
Section: Introductionmentioning
confidence: 99%
“…Iniciativas como o Cameleon Framework Reference (CFR) [Meixner et al, 2011] servem como referência para projetar e classificar métodos e arquiteturas de interfaces baseadas em modelos, levando em conta o suporte a diversos contextos…”
Section: Lista De Figurasunclassified